Warm-up for sprint swimming: Race-pace or aerobic stimulation? A randomized study - Neiva, H. P.; Marques, M. C.; Barbosa, T. M.; Izquierdo, M.; Viana, J. L.; Teixeira, A. M.; Marinho, D. A. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to compare the effects of 2 different warm-up intensities on 100-m swimming performance in a randomized controlled trial. Thirteen competitive swimmers performed two 100-m freestyle time-trials on separate days after either control or experimental warm-up in a randomized design. The control warm-up included a typical race-pace set (4 × 25 m), whereas the experimental warm-up included an aerobic set (8 × 50 m at 98-102% of critical velocity). Cortisol, testosterone, blood lactate ([La-]), oxygen uptake (VO2), heart rate, core (Tcore and Tcorenet) and tympanic temperatures, and rating of perceived exertion (RPE) were monitored. Stroke length (SL), stroke frequency (SF), stroke index (SI), and propelling efficiency (Eta p) were assessed for each 50-m lap. We found that VO2, heart rate, and Tcorenet were higher after experimental warm-up (d > 0.73), but only the positive effect for Tcorenet was maintained until the trial. Performance was not different between conditions (d = 0.07). Experimental warm-up was found to slow SF (mean change ±90% CL = 2.06 ± 1.48%) and increase SL (1.65 ± 1.40%) and Eta p (1.87 ± 1.33%) in the first lap. After the time-trials, this warm-up had a positive effect on Tcorenet (d = 0.69) and a negative effect on [La-] (d = 0.56). Although the warm-ups had similar outcomes in the 100-m freestyle, performance was achieved through different biomechanical strategies. Stroke length and efficiency were higher in the first lap after the experimental warm-up, whereas SF was higher after control warm-up. Physiological adaptations were observed mainly through an increased Tcore after experimental warm-up. In this condition, the lower [La-] after the trial suggests lower dependency on anaerobic metabolism.